The digital era and communication competencies of healthcare professionals - Miljković, Ana (General Practice, 2025)
Introduction: Communication skills are the cornerstone of effective general practice, influencing the quality of diagnosis, therapy, and the establishment of trust with patients. The rapid development of digital technologies in recent years has transformed the way information is exchanged within healthcare systems, creating new opportunities while raising challenges in maintaining empathy, ethical standards, and continuity of communication. Aim: To present modern approaches and challenges in communication between physicians and patients in the digital era, with a focus on the use of artificial intelligence, virtual reality, and other technological solutions to enhance healthcare professionals’ communication skills. Methods: This study is a narrative literature review. Searches were conducted in PubMed, Scopus, and Google Scholar for the period January 2018 – July 2025, using the keywords: communication skills, digital health, artificial intelligence, virtual reality, telemedicine, patient–doctor communication. The analysis included publications in Serbian and English, as well as the author’s personal experience in clinical practice and teaching. Results: Communication skills are essential for high-quality medical practice [1–3]. Digital technologies such as artificial intelligence, telemedicine, VR, and AR offer new possibilities but also pose challenges related to ethics, empathy, and data protection [4–9]. ChatGPT can facilitate the transfer of complex information to patients, while immersive technologies improve healthcare professionals’ training [7,8,10–12]. Live streaming accelerates communication in emergency situations but requires clear and precise information exchange [5,6]. Conclusion: Technological advancements can improve physician–patient communication, but only when applied with preserved empathy, adherence to ethical principles, and continuous professional development of healthcare workers.